2000
DOI: 10.1046/j.1365-2222.2000.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP kinase regulates TNFα‐, IL‐1α‐ and PAF‐induced RANTES and GM‐CSF production by human bronchial epithelial cells

Abstract: These results indicate that p38 MAP kinase plays an important role in TNF alpha-, IL-1 alpha- or PAF-activated signalling pathway which regulates RANTES and GM-CSF production by BECs and that the specific inhibitor for p38 MAP kinase activity might be useful for the treatment of allergic inflammation of the airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…p38 MAPK inhibition affected the PDT-induced expression of immune and inflammatory response mediators, such as COX-2 (PTGS2), GM-CSF (granulocyte macrophage colony-stimulating factor; CSF2), interleukin 8 (IL8) and the Toll-like receptor 2, as also reported in previous studies (Hashimoto et al, 2000;Hoffmann et al, 2002;Imasato et al, 2002). Notably, the expression of a number of stress-responsive genes encoding antioxidant and Phase II drug-metabolizing enzymes (Table 2), with an established role in cellular protection following oxidative damage caused by ROS or electrophiles (Lee and Johnson, 2004) was found to be significantly attenuated by PD169316.…”
Section: Global Distribution Of Hypericin-pdt Differentially Expressesupporting
confidence: 76%
See 1 more Smart Citation
“…p38 MAPK inhibition affected the PDT-induced expression of immune and inflammatory response mediators, such as COX-2 (PTGS2), GM-CSF (granulocyte macrophage colony-stimulating factor; CSF2), interleukin 8 (IL8) and the Toll-like receptor 2, as also reported in previous studies (Hashimoto et al, 2000;Hoffmann et al, 2002;Imasato et al, 2002). Notably, the expression of a number of stress-responsive genes encoding antioxidant and Phase II drug-metabolizing enzymes (Table 2), with an established role in cellular protection following oxidative damage caused by ROS or electrophiles (Lee and Johnson, 2004) was found to be significantly attenuated by PD169316.…”
Section: Global Distribution Of Hypericin-pdt Differentially Expressesupporting
confidence: 76%
“…Thus, the p38 MAPK pathway in PDT-treated T24 cells could rapidly stabilize and increase translation of AREs-containing labile mRNAs, for example, for MMP-13, COX-2 and GM-CSF, involved in tumor promotion (Hashimoto et al, 2000;Hoffmann et al, 2002;Dean et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although airway epithelial cells are well recognized as potent sources of cytokines such as IL-6, IL-8 (5, 19), IL-16 (1), GM-CSF (5,19,26), TGF-␤ (12, 18), endothelin-1 (23), RANTES (8), and eotaxin (16), little is known regarding the effects of culture technique and cellular differentiation on the capacity of the airway epithelium to produce these factors under baseline conditions, or in response to cytokines present in the asthmatic airway. Whereas previous reports have demonstrated that NHBE cells produce GM-CSF and TGF-␤ 2 under baseline conditions, and increase production of both under the influence of Th2 cytokines (20,31), these reports have been limited to submerged monolayer cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the current authors have shown previously that human bronchial epithelial cells respond to interleukin (IL)-4 and IL-13 with tyrosine phosphorylation of STAT (signal transducer and activator of transcription)6 mediated by members of the JAK (Janus kinase) family [20]. Bronchial epithelial cells also respond to environmental stress and endogenous cytokines, such as tumour necrosis factor (TNF)-a and IL-1b through activation of p38 MAPK [21] and jun N-terminal kinase (JNK) [22].…”
mentioning
confidence: 91%